KNOWLEDGE, VALUABLE CONCEPTS AND THE PRESERVATION OF THE ENVIRONMENT - Trujillo Meza, Julio Cesar (2016)
Attendance at the event programmed by Alafec and the University of Texas Rio Grande Valley- Bronwsville, was for the particular interest of continuing international mobilizations. The first, was in the Republic of Panama on the bioethical reasoning applied to socially responsible companies; and this second opportunity was to validate and investigate a research methodology using the SPSS program for statistical procedures and to know the scientific process to carry out empirical research and the analysis corresponding to lead the results of such research.The investigation began with a series of study samples where the variables -dependent and independent- were considered. Were submitted 758 samples to the analysis and the concepts related to: Responsible consumption; Fair trade; Food sovereignty; Sustainable development and the contribution to the preservation of the environment in Latin America.